Word stress effects on syllable onset in Brazilian Portuguese - Cantoni, Maria M.; Prado, Vitor A. M. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2024: Anais do XV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2023.234143, 2024)
This study addresses duration patterns related to Brazilian Portuguese word stress. It has been generally assumed that stress affects some parts of the syllable, such as the vowel, but not others, like the consonant that precedes it. In this study, experimental data was used to test to what extent the consonant in a syllable onset is affected by stress. Results show that in stressed syllables consonants are longer than in post-stressed syllables. The lengthening impacts fricatives, nasals and even plosives.